A homogenization-based damage model for stiffness loss in ductile metal-matrix composites. (April 2020) - Dorhmi, Khaoula; Morin, Léo; Derrien, Katell; Hadjem-Hamouche, Zehoua; Chevalier, Jean-Pierre
Abstract: The aim of this paper is to develop a homogenized model that permits to describe the progressive loss of stiffness observed experimentally on ductile metal-matrix composites subjected to mechanical loadings. A two-step homogenization procedure is proposed to describe the effect of damage on the elastic properties. Since damage is solely driven by plastic deformation, a Gurson-type model is considered to describe the nucleation and growth of voids. Completed by appropriate evolution equations of the microstructure, this model of plasticity is used to update the elastic properties that are described by a mean-field homogenization scheme. The complete incremental model is implemented numerically and applied to the prediction of the stiffness loss. The model predictions are in very good agreement with experimental results on Al-SiC composites, cast irons and steel composites.